Experiments in participation - Lezaun, J; Marres, N; Tironi, M (MIT Press, 2017)
This chapter discusses the emerging body of work in STS that explores the experimental dimension of public participation in contemporary societies. This work moves beyond the original focus of STS on the role of experimentation in the sciences to consider the proliferation of experimental formats in the arts, social movements, economic organization, and public life. The chapter outlines several strands of scholarship that, through the study of experiments, have developed a materialist, situational and performative understanding of the making of publics in technological societies. At the heart of this scholarship lies a formative ambiguity: the fact that experiments in participation operate as both an object of inquiry and a device that actors including researchers themselves can deploy for the creation of new collectives. After reviewing how a focus on experimental situations was instrumental to the emergence of STS as a distinctive mode of inquiry, the chapter elaborates three recent themes from the literature: object-centered engagement, inventive methods, and prototyping. The chapter concludes by arguing that experiments in participation represent a crucial nexus of theory and practice in contemporary science, technology and society, one that allows the field to expand its repertoire of political tools and participate in wider experimental cultures.